2022
DOI: 10.2174/1874467214666211130162152
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Edaravone on MicroRNA Expression in Exosomes after Hepatic Ischemia-reperfusion Injury

Abstract: Background and Objective: Hepatic ischemia-reperfusion injury (HIRI) results in serious complications after liver resection and transplantation. Edaravone (ED) has a protective effect on IRI. This study was designed to evaluate whether ED could protect the liver of rats from HIRI injury and explored its exosomal miRNA-related mechanism. Methods: The sham group, hepatic ischemia/reperfusion (IR group), and hepatic ischemia/reperfusion + edaravone (ED group) models were established. We determined the protecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Nucleic acids or proteins in body fluid-derived exosomes may alleviate or aggravate HIRI. Fei et al (2021) performed nextgeneration sequencing (NGS) of miRNAs in plasma-derived exosomes and verified that miRNAs-PC-3p-190-42101 in exosomes could reduce the levels of inflammatory factors and protect the liver from HIRI. In a rat model of HIRI, Ashour et al (2021) reported that plasma exosomes had increased levels of miR-687, in addition to increased levels of liver tissue inflammatory markers and caspase-3.…”
Section: Body Fluid-derived Exosomesmentioning
confidence: 96%
“…Nucleic acids or proteins in body fluid-derived exosomes may alleviate or aggravate HIRI. Fei et al (2021) performed nextgeneration sequencing (NGS) of miRNAs in plasma-derived exosomes and verified that miRNAs-PC-3p-190-42101 in exosomes could reduce the levels of inflammatory factors and protect the liver from HIRI. In a rat model of HIRI, Ashour et al (2021) reported that plasma exosomes had increased levels of miR-687, in addition to increased levels of liver tissue inflammatory markers and caspase-3.…”
Section: Body Fluid-derived Exosomesmentioning
confidence: 96%